Investigating the Effect of Gender on Academic Achievement and Career Aspirations in Secondary Education in Bauchi Metropolis Bauchi State Nigeria - Anas Babangida; Sulaiman Abubakar; Muhammad Yusuf Gidado (Balai Publikasi Indonesia, 2026)
This study investigated the effect of gender on academic achievement and career aspirations among secondary school students in Bauchi Metropolis, Bauchi State. The objectives were to determine the career aspirations of male and female students, examine their perceptions regarding career choices, assess the relationship between gender and career aspirations, and identify the influence of gender stereotypes on academic achievement and career decisions. A descriptive survey research design was adopted. The population comprised students from ten public senior secondary schools, while a sample of 306 respondents was selected using sampling techniques. Data were collected using a structured close-ended questionnaire based on a four-point Likert scale. The data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics involving Pearson Product Moment Correlation at a 0.05 level of significance. The findings revealed a significant relationship between gender and career aspirations, with gender stereotypes influencing students’ academic achievement and occupational preferences. Male students showed stronger inclination toward STEM-related careers, while female students preferred caregiving and social service professions. The study concludes that gender remains a key determinant of academic and career outcomes among secondary school students in Bauchi Metropolis. The study recommends the strengthening of school-based career guidance services and the training of teachers as career mentors to support students in making informed, stereotype-free career decisions